Sleep quality and influencing factors among nursing students: A cross-sectional survey from the United Arab Emirates - Ramya Kundayi Ravi; Mona Mohamed (Kashan University of Medical Sciences, 2024)
Background: Sleep is a fundamental and essential process that has a significant impact on our physiological and cognitive functioning. Adequate sleep quality and quantity are crucial for improving attention, memory, insight, concentration, decision-making, speech, and, most importantly, learning and memory.Objectives: This study aimed to evaluate sleep quality and identify associated factors among undergraduate nursing students.Methods: A cross-sectional survey was conducted with 237 nursing students recruited from a selected university in Ras Al Khaimah, UAE, using a convenience sampling technique from February to October 2022. Data were collected using a structured sociodemographic and lifestyle questionnaire, along with the Pittsburgh Sleep Quality Index (PSQI). Descriptive statistics were employed to summarize the data, while independent sample t-tests and one-way analysis of variance were used to examine differences in mean sleep quality scores between groups.Results: The global PSQI scores ranged from 0 to 21, with a mean of 6.54±3.2. Nearly three-fourths (73%) of the participants were classified as poor sleepers based on their global PSQI scores. The average duration of self-reported nighttime sleep was 6.61±1.76 hours. More than one-third (36.7%) of participants reported a sleep efficiency of less than 85%, and only 33.8% felt sufficiently enthusiastic to complete their tasks. Poor sleep quality was significantly associated with watching television for more than two hours on weekends (p=0.044).Conclusion: A substantial proportion of undergraduate nursing students experience poor sleep quality. It is essential to raise awareness about the importance of adequate sleep and the consequences of poor sleep among this population.